Limitations and Scope of the Government's Role in Law Number 1 of 2024 concerning Electronic Information and Transactions - Simanjuntak, Jimmy (Penerbit Mandalika Indonesia, 2025)
The government has an important role in maintaining digital space. This certainly cannot be denied by anyone regarding the role of the government in supervising the actions of the community. However, the community must also be active in supervising the role of the government in digital media. This action is part of the participation of the community and government in managing digital space based on applicable national laws. The government in carrying out supervision is prohibited from limiting the space for community freedom in digital space. The government's authority in digital space must be supervised as it should be, so that threats to public order are maintained. Telematics law in Indonesia with its development continues to increase government authority in digital space so that through this, the community must create boundaries regarding government efforts in enforcing the law and government actions that exceed the limits of its authority in digital space.